Fleiss’s Kappa: Assessing the Concept of Technology Enabled Active Learning (TEAL) - Hassan, Nur Farha Bte; Puteh, Saifullizam Bin; Muhamad Sanusi, & Amanina Binti (Journal of Technical Education and Training, 2019)
Technology Enabled Active Learning (TEAL) is a platform to produce a quality student and improve their academic performance, promotes skills development and increases satisfaction in the learning experience. TEAL also promote marketability skill using technology to become excellent workers in industries. Many researchers have found that concept of TEAL need to be apply in education in order to give chance for student to explore their own studies using technology in a few approach learning (i.e., online, blended, collaborative, practical and interactive learning). Nevertheless, several studies have reported that TEAL is effective approach to make sure student active to join the own activities class to complete their studies. Based on previous findings, five categories of TEAL were identified. This study identifies the important elements of TEAL needs in active learning among assessor’s agreement. The aim is to measure the interrater reliability between five (5) assessors of stakeholder in academic fields. This study measures assessor’s agreement by using Fleiss’s Kappa statistical method. The results show that all assessors agreed with 47 elements in each of construct and 12 elements that do not agree by them. In conclusion, the study recommends the application of TEAL needs in teaching and learning (TnL) process to implement active learning, that more focus on student involve in activity lesson by using technological equipment for generate their knowledge, skill and understanding in their fields. Findings from this study show that all assessors agreed with all of the categories which is suitable for elements of TEAL.